Abdij van Park (2024)
Keywords: park

Mozes en zijn broer Aaron : een buitengewone cyclus 13de-eeuwse muurschilderingen ontdekt in de kapittelzaal van de Parkabdij - Bergmans, Anna; De Clercq, Lode; Lagaert, Joke (M&L: Monumenten en Landschappen, 2022)
Moses and his brother Aaron. The discovery of an exceptional cycle of 13th-century wall paintings in Park Abbey’s chapter house The Premonstratensian Park Abbey in Heverlee (Leuven) has already been studied and restored for many years. With each interior intervention, there have been major surprises. In 2017, during ongoing preliminary investigations, the city of Leuven ordered some additional probes for the chapter house, mainly to locate the original access to this room from the cloister. This research soon led to the discovery of painted fragments, which then asked for more extensive studies. Here, the entire original space of the chapter house was involved. Some very fine remains of a unique decor were thus revealed. This discovery offers a completely new dimension to the chapter house of Park Abbey, which is unique in Belgium. The east wing of the cloister, in which the chapter house is located, was built in the same period as the western part of the church, namely the second half of the 13th century. During the 16th century the chapter house was thoroughly rebuilt and redecorated. However, the preliminary investigation showed that there were still considerable fragments of medieval murals on the walls. On the western wall, several biblical figures can be distinguished. Moses with the tablets of the law points to the idolatrous dragon-like devil on a pillar. To his right stands his brother Aaron holding his attribute, a flaming fire. Next to him appears their sister Myriam. A little further north, the bearded man may be one of the Three Kings. These figures point to a cycle evolving from Old to New Testament with Biblical characters as prefigures. Also very beautiful is the preserved architectural polychromy on the Gothic openings between the cloister and the chapter house. On the east wall, among other things, there are some beautiful fragments of painted frames around closed oculi. The painted ensemble, dating from the second half of the 13th century, is designed as a whole, both iconographically and in terms of style and technique. The figures in the upper register are framed with a monumental frieze. In this way, a continuous band with figures was created. The extent of the paintings and the rather good condition in which they have been preserved, make the Park Abbey’s chapter house quite exceptional and unique. In view of the future museum function of the abbey complex, the presentation of these to the public will be of great value.
Keywords: park

Vroege receptiesporen van Van den vos Reynaerde en Spiegel historiael op een onbekend fragment in de Abdij van Park (Heverlee, Archief Abdij van Park, VIIIB20/120) - Breeus-Loos, Laurent; Van Eldere, Irene (Spiegel der letteren, 2022)
Keywords: park

Het Missaal van Park (Oxford, Wadham College, Ms. A.14.12). Een liturgisch boek in opdracht van Ambroos van Engelen, abt van Park - Kügle, Karl (Als de bliksem. 900 jaar norbertijnen en norbertinessen, 2021)
Keywords: park

'Scriptus est liber iste in honore Sanctae Mariae in Parcho'. De Parkbijbel uit 1148 - Macarenko, Aleuna (Als de bliksem. 900 jaar norbertijnen en norbertinessen, 2021)
Keywords: park

Indrukwekkende reeks glasramen van Jan de Caumont voor de pandgang van de Parkabdij - Rambaut, Aletta (Als de bliksem. 900 jaar norbertijnen en norbertinessen, 2021)
Keywords: park

'Vrije conste dewelcke nyet gemeyns en heeft met eenige andere ambachten'. Jan Christiaan Hansche in de Parkabdij - Van Vaeck, Marco (Als de bliksem. 900 jaar norbertijnen en norbertinessen, 2021)
Keywords: park